Synthesis of 4-Arylallylidenepyrazolone Derivatives - Esteban Aguilar-Llanos; Juan Carlos Romero-Benavides; Jorge Heredia-Moya (Chemistry Proceedings, 2021)
Pyrazoles and their derivatives have attracted particular attention because they have a wide variety of biological activities, and recently, we found that 4,4’-(arylmethylene)-bis-(1-phenyl-3-methyl-1H-pyrazole-5-ols) have good leishmanicidal activity against promastigotes of Leishmania mexicana. 4-Arylidenepyrazolone derivatives also have antiparasitic activity and are intermediates in the synthesis of these bispirazoles that are formed by the equimolar reaction of 3-methyl-1-phenyl-2-pyrazoline-5-one with aromatic aldehydes. In order to obtain new compounds with potential leishmanicidal activity, we attempted to synthesize several 4-arylallylidenepyrazolone derivatives through the reaction of pyrazol-3-one with different cinnamaldehydes. We report here the study of the synthesis of some 4-arylallylidenepyrazolone derivatives from the reaction between 5-methyl-2-phenyl-2,4-dihydro-3H-pyrazol-3-one and 4-nitrocinnamaldehyde. We found that L-proline and FeCl3 were the best catalysts, and we also observed a solvent effect in the reaction. Our preliminary results indicate that aprotic solvents favor the formation of the 2Z isomer instead of the 2E isomer.